The Problem Of Multicultural Attitudes in Fourth Grade Students - Farsya Shabirah; Ahmad, Mubarak (Jurnal Elementaria Edukasia, 2024)
Multiculturalism is a response to the growing primary school population and demands for equal rights for all primary schools. Through this education, students are taught to avoid discrimination, understand tolerance, respect other people's views, build empathy, and create a culture of mutual respect. This research is motivated by awareness of the importance of multicultural attitudes that occur in elementary school students. The aim of this research is to find out what problems arise in the interactions of students who interact in a multicultural atmosphere at school. To explore the issue of multicultural attitudes in elementary schools, this research uses a case study method. Data was obtained through observation, interviews and documentation which was analyzed using tabulation and comparison techniques to obtain conclusions from the data. The subjects of this research were fourth grade teachers and 5 students. The results of the research concluded that the problem of multicultural attitudes still often occurs in elementary schools, especially in interactions between students. These problems include making jokes that offend beliefs/religions, offensive jokes can hurt the feelings of students whose religion is used as material for encouragement. This can cause low self-esteem, anxiety, and discomfort in the school environment. Another problem found was mocking parents' professions, which has the potential to make students feel embarrassed, low self-esteem, and have problems socializing because their parents' professions are used as material for socializing. The problem of dominant multicultural attitudes occurs when students interact outside of study hours.